In-patient satisfaction with nursing care: Outcome measurement in a tertiary health facility in Lagos, Nigeria - Oluwafunmilola Mary Mobolaji-Olajide; Stella Chinma Adereti; Patience Omonigho Odutayo; Prisca Olabisi Adejumo (Elsevier, 2020)
Patient satisfaction with nursing care is an important predictor of outcome of nurses' ability to meet individualized needs of patients. This study evaluated level of satisfaction of in-patients and determined factors influencing their satisfaction with nursing care. A quantitative descriptive cross-sectional design was adopted. One hundred and thirty-one (131) in-patients participated from a simple randomly selected teaching hospital in Lagos. Two Instruments; Patients' Perception of Hospital Experience with Nurses (PPHEN) with 20 items and Self-administered structured questionnaire were used to collect data.Respondents' age ranged between 18 years and 65 years with mean age of 38 years ± 14. Majority of respondents were female (56.5%), married (48.9%), from Yoruba tribe (63.4%) and had tertiary education (47.4%). Majority (81.7%) had high level of satisfaction with nursing care. Factors that influenced patients' satisfaction with nursing care includes individualized care, Patient feeling accepted by nurses, nurses' reassurance, Early discharge plan, quick response to patient's needs, good knowledge of conditions, good nurse/patient relationship, improved self-esteem, timely medications, relative involvement in patient's care and nurses cheerful & gentle approach to care. There was a significant association between in-patient satisfaction and patients' ethnic group and educational levels at p value = 0.03 respectively. The study concluded that majority of in-patients in selected care setting had high level of satisfaction (81.7%) with nursing care. There is need for further investigation on nurses' attributes that promoted satisfaction among hospitalized patients to take care of patients with low (3.8%) and moderate (14.5%) level of satisfaction.